Revision to Nomenclature of the Zarah Subgroup of the Kansas City Group (Pennsylvanian) in Kansas - Oborny, Stephan; Layzell, Anthony; Ludvigson, Greg; Hasiuk, Franek (Midcontinent Geoscience, 2022)
This paper provides a summary review of proposed nomenclatural revisions to the Zarah Subgroup of the Kansas City Group (Pennsylvanian) in Kansas and outlines changes adopted by the Kansas Geological Survey. The Iola Limestone, which comprises in ascending order the Paola Limestone, Muncie Creek Shale, and Raytown Limestone Members, is now considered the basal formation of the Zarah Subgroup. We reinstate the overlying Liberty Memorial Shale as originally defined by Clair (1943) in the area of Kansas City, Missouri. We also restrict the Wyandotte Limestone to include only, in ascending order, the Frisbie Limestone, Quindaro Shale, and Argentine Limestone Members. Furthermore, the Lane Shale is restricted in use and encompasses all strata within the shale-dominated interval between the top of the Argentine Limestone Member of the Wyandotte Limestone and the base of the overlying Plattsburg Limestone. Within the revised Lane Shale, the KGS now formally recognizes, in ascending order, the Lower Farley Limestone, Middle Farley Shale, and Upper Farley Limestone Members. The Bonner Springs Shale is now demoted in rank and included as the uppermost member within the Lane Shale.